BS ISO 12925-2. Lubricants, industrial oils and related products (class L). Family C (Gears). Part 2. Specifications of categories CKH, CKJ and CKM (lubricants open and semi-enclosed gear systems) (11th February 2020) - British Standards Institution,
No abstract available